Research of the Causes and Risk Factors of Autism in the Western Region of Algeria - Mehida, Hayet; Meziani, Samira; Mehida, Wahiba; Zemri, Khalida; Bekhaled, Imene; Bendahmane, Malika (Journal of Drug Delivery and Therapeutics, 2020)
Introduction Autism is a neurodevelopmental disorder that manifests before 3 years old and affects many areas, communication, social interactions and behaviors. In Algeria, there has not yet been a regional or national epidemiological investigation concerning autism spectrum disorders.Materials and methods: Our study was carried about 100 patients ( autistic children) in the western region of Algeria, in order to determine the differents risk factors involved in the onset of autism syndrome.Results and discussion: The obtained results indicate a male predominance with a sex ratio of 4: 1 and the degree of reached is average in 44% of patients. 42% of the patients are youngsters. Parents' worry about their children begins  between 24 and 36 months. The parents' advanced age at conception, stress, presence of certain pathologies and drug intake by mothers, as well as fetal distress at birth and children's exposure to screens were the main risk factors. Repetitive movements, lack of social communication, language delay, and lack of visual fixation were the main clinical symptomatology.Conclusion: This study allowed us to detect the main factors associated with the onset of autism. However, the results obtained cannot be generalized to the entire population.Keywords: Autism, autism spectrum disorder, risk factors, clinical symptoms, western region of Algeria.